Multimedia dan islam (K.Lumpur Institut Kefahaman Islam Malaysias, 2000)
On Malaysian Muslim community and issues on multimedia computing; collection of articles.
Includes bibliographical references and index.
Keywords: Computers -- Religious aspects -- Islam; Islam and science; Multimedia systems; Multimedia systems - Religious aspects - Islam; Multimedia systems in management; Multimedia systems -- Indonesia